(untitled) (Biological Sciences - PJSIR, 2004)
12:0 20:0 18:2 Two local varieties of Hordeum vulgare Jao 87, and Jao 83 were studied for their lipid classes and fatty acid composition. Total barley lipids were solvent extracted and classified into their respective classes with the help of silicic acid gel column chromatography. Each lipid class was further fractionated by thin layer chromatography, and after methylation, its fatty acid composition was determined by gas chromatography. The lipid contents were 3-3.2% of the total barley weight in both the varieties. The percentages of neutral lipids, glycolipids and phospholipids, were 70, 10 and 20%, respectively. Gas chroma- tography showed the presence of fatty acids from series lauric (C ) to arachidic (C ) while linoleic acid (C ) was the principal fatty acid in all the classes with a few exceptions.